2024
DOI: 10.1002/ps.7976
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione biosynthesis is involved in metamorphosis, antioxidant function, and insecticide resistance in Tribolium castaneum

KumChol Kim,
Han Gao,
Chengjun Li
et al.

Abstract: BACKGROUNDReduced glutathione (GSH) synthesis is vital for redox homeostasis, cell‐cycle regulation and apoptosis, and immune function. The glutamate–cysteine ligase catalytic subunit (Gclc) is the first and rate‐limiting enzyme in GSH synthesis, suggesting the potential use of Gclc as a pesticide target. However, the functional characterization of Gclc, especially its contribution in metamorphosis, antioxidant status and insecticide resistance, is unclear in Tribolium castaneum.RESULTSIn this study, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…As shown in Figure , the larval mortality in the ZINC000032992384-treated group was 63.8% at 100 μM, which was significantly higher than that of the positive control, dichlorvos-treated group (29.1%) ( p < 0.01). Moreover, most of the larvae in the acetone-treated group (93.6%) were developed normally (Figure B), while those in the ZINC000032992384 and dichlorvos-treated groups were less developed and died (Figure C), which is similar to our previous findings that TcGclc knock-down caused metamorphosis deficiency .…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…As shown in Figure , the larval mortality in the ZINC000032992384-treated group was 63.8% at 100 μM, which was significantly higher than that of the positive control, dichlorvos-treated group (29.1%) ( p < 0.01). Moreover, most of the larvae in the acetone-treated group (93.6%) were developed normally (Figure B), while those in the ZINC000032992384 and dichlorvos-treated groups were less developed and died (Figure C), which is similar to our previous findings that TcGclc knock-down caused metamorphosis deficiency .…”
Section: Resultssupporting
confidence: 89%
“…Moreover, most of the larvae in the acetone-treated group (93.6%) were developed normally (Figure B), while those in the ZINC000032992384 and dichlorvos-treated groups were less developed and died (Figure C), which is similar to our previous findings that TcGclc knock-down caused metamorphosis deficiency . The result showed that ZINC000032992384 caused a deficiency in metamorphosis and antioxidant activity by inhibition of TcGclc activity and showed insecticide activity.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations